A creep model for ultra-deep salt rock considering thermal-mechanical damage under triaxial stress conditions - Chao Liang; Jianfeng Liu; Jianxiong Yang; Huining Xu; Zhaowei Chen; Lina Ran (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
To investigate the specific creep behavior of ultra-deep buried salt during oil and gas exploitation, a set of triaxial creep experiments was conducted at elevated temperatures with constant axial pressure and unloading confining pressure conditions. Experimental results show that the salt sample deforms more significantly with the increase of applied temperature and deviatoric loading. The accelerated creep phase is not occurring until the applied temperature reaches 130 °C, and higher temperature is beneficial to the occurrence of accelerated creep. To describe the specific creep behavior, a novel three-dimensional (3D) creep constitutive model is developed that incorporates the thermal and mechanical variables into mechanical elements. Subsequently, the standard particle swarm optimization (SPSO) method is adopted to fit the experimental data, and the sensibility of key model parameters is analyzed to further illustrate the model function. As a result, the model can accurately predict the creep behavior of salt under the coupled thermo-mechanical effect in deep-buried condition. Based on the research results, the creep mechanical behavior of wellbore shrinkage is predicted in deep drilling projects crossing salt layer, which has practical implications for deep rock mechanics problems.